The Central Slave Basement Complex, Part II: age and tectonic significance of high-strain zones along the basement-cover contact - Bleeker, Wouter; Ketchum, John WF; Davis, W J (Canadian Journal of Earth Sciences, 1999)
The basement-cover high-strain zone enveloping parts of the Sleepy Dragon Complex, northeast of Yellowknife, Slave Province, Canada, has been reinvestigated. Integrated stratigraphic, structural, and geochronological data show that the high-strain zone is of regional extent and is best interpreted as a décollement between crystalline, ca. 2.9-3.3 Ga rocks of the Central Slave Basement Complex and pre-2687 Ma cover rocks. Three temporally distinct mafic dyke swarms occur within the high-strain zone. The two oldest of these constrain the timing of the high-strain event to between 2734 ± 2 and 2687 ± 1 Ma. At the time of décollement development, the cover stratigraphy consisted of (i) the Central Slave Cover Group, a thin, pre-2734 Ma succession of mafic and ultramafic volcanic rocks, conglomerates, fuchsitic quartzites, minor rhyolites, and banded iron formation; and (ii) an overlying sequence of tholeiitic pillow basalts. The Central Slave Cover Group is considered to be autochthonous, whereas a variety of evidence suggests that the pillow basalts are parautochthonous to possibly allochthonous. The transport direction in the décollement was from northeast to southwest, and maximum displacement was probably on the order of 10 to several tens of kilometres. Presently, the décollement appears discontinuous due to younger intrusive and erosional events. Around most of the southern flanks of the Sleepy Dragon Complex, the crystalline core of the complex consists of post-décollement intrusive rocks and (or) is unconformably overlain by parts of the Yellowknife Supergroup that are younger than 2687 Ma. Lineation patterns in these younger rocks reflect regional deformation events that postdate and are unrelated to the décollement. The new data allow two tectonic models for development of the décollement: (i) a contractional thrusting model, involving collision of an eastern Slave Province arc terrane; or (ii) a syn-greenstone belt extensional model.